Polyfunctional T cell responses in children in early stages of chronic Trypanosoma cruzi infection contrast with monofunctional responses of long-term infected adults. - María C Albareda; Ana M De Rissio; Gonzalo Tomas; Alicia Serjan; María G Alvarez; Rodolfo Viotti; Laura E Fichera; Mónica I Esteva; Daniel Potente; Alejandro Armenti; Rick L Tarleton; Susana A Laucella (Public Library of Science (PLoS), 2013)
Background Adults with chronic Trypanosoma cruzi exhibit a poorly functional T cell compartment, characterized by monofunctional (IFN-γ-only secreting) parasite-specific T cells and increased levels of terminally differentiated T cells. It is possible that persistent infection and/or sustained exposure to parasites antigens may lead to a progressive loss of function of the immune T cells. Methodology/principal findings To test this hypothesis, the quality and magnitude of T. cruzi-specific T cell responses were evaluated in T. cruzi-infected children and compared with long-term T. cruzi-infected adults with no evidence of heart failure. The phenotype of CD4(+) T cells was also assessed in T. cruzi-infected children and uninfected controls. Simultaneous secretion of IFN-γ and IL-2 measured by ELISPOT assays in response to T. cruzi antigens was prevalent among T. cruzi-infected children. Flow cytometric analysis of co-expression profiles of CD4(+) T cells with the ability to produce IFN-γ, TNF-α, or to express the co-stimulatory molecule CD154 in response to T. cruzi showed polyfunctional T cell responses in most T. cruzi-infected children. Monofunctional T cell responses and an absence of CD4(+)TNF-α(+)-secreting T cells were observed in T. cruzi-infected adults. A relatively high degree of activation and differentiation of CD4(+) T cells was evident in T. cruzi-infected children. Conclusions/significance Our observations are compatible with our initial hypothesis that persistent T. cruzi infection promotes eventual exhaustion of immune system, which might contribute to disease progression in long-term infected subjects.